Formulation of Once a Day Controlled Release Tablet of Indomethacin Based on HPMC-Mannitol - Pradhan, Roshan; Budhathoki, Uttam; Thapa, Panna (Kathmandu University Journal of Science, Engineering and Technology, 2010)
p>A hydroxypropyl methylcellulose (HPMC K4M, HPMC K15M, and HPMC K100M) matrix tablet containing Indomethacin along with mannitol was formulated as a function of HPMC viscosity, and was compared with the commercial products. The release characteristics of the matrix tablet were investigated in the intestinal fluid, 6.8 pH phosphate buffer for 12 hours. The formulated products and two marketed products as reference sample were studied for its different physicochemical parameters and in vitro dissolution studies. It was found that the drug release profile decreases with increase in viscosity of polymer and, with increase polymer level in the formulations. Matrix tablets formulated employing Drug:HPMC K15M:mannitol::1:0.25:1 and Drug:HPMC K15M:mannitol::1:0.25:2 gave slow release of indomethacin spread over 12 hours and their dissolution profiles were compared with the Indian marketed product. The dissolution profiles of both the formulations were similar to the dissolution profile of the marketed product, the similarity factor being 74.59 and 68.04 respectively. The dissolution profiles of formulations containing same viscosity grade of HPMC in remarkably different concentrations and different viscosity grade of HPMC in same concentrations were different. Key words: Indomethacin; Controlled release; Hydroxypropyl methyl cellulose; Mannitol; Dissolution. DOI: 10.3126/kuset.v4i1.2884 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 55-67